“Porcelain of the Second Row”: Interior Plastic Art Factories and their Role in the Development of the Leningrad Art Industry in the 1950s - Sapanzha, Olga S. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2024)
This article presents an analysis of the activities of the Leningrad art industry enterprises of the 1950s, which produced a range of interior porcelain products. The advent of a network of such industries was enabled by a shift in the function and position of small-scale plastic art forms within the domestic sphere, marking the inception of the process of establishing a conventional residential environment. The initial phase of the process entailed the incorporation of minute details within the domestic setting, including artefacts and creations produced through factory or artisanal methods. These elements were to assume a significant role within the interior. From 1952–1954, there was a notable increase in the assortment and circulation of smaller porcelain plastic pieces. The network of porcelain enterprises was expanding, each of which solved the problems of design and manufacture of small sculpture. The analysis of the enterprises of Leningrad in the 1950s allowed us to identify four types of production, in the structure of which were shops for the production of artistic porcelain. The first category was comprised of enterprises engaged exclusively in the production of artistic porcelain, including limited-edition and unique author’s samples (in Leningrad, Lomonosov Leningrad Porcelain Factory). The second type was enterprises of the porcelain industry focused on the production of technical porcelain, and having in their structure a workshop to produce artistic porcelain (in Leningrad, Leningrad Factory of Porcelain). The third type included enterprises that produced sanitary porcelain and a small amount of artistic porcelain (in Leningrad, Stroyfayans Factory). The fourth type was cooperative production that along with artistic porcelain, sold a wide range of household goods made of various materials (in Leningrad, Progress Artel).